Cost‐Effectiveness of Orthogeriatric and Fracture Liaison Service Models of Care for Hip Fracture Patients: A Population‐Based Study. (1st November 2016) - Leal, Jose; Gray, Alastair M; Hawley, Samuel; Prieto‐Alhambra, Daniel; Delmestri, Antonella; Arden, Nigel K; Cooper, Cyrus; Javaid, M Kassim; Judge, Andrew
ABSTRACT: Fracture liaison services are recommended as a model of best practice for organizing patient care and secondary fracture prevention for hip fracture patients, although variation exists in how such services are structured. There is considerable uncertainty as to which model is most cost‐effective and should therefore be mandated. This study evaluated the cost‐ effectiveness of orthogeriatric (OG)‐ and nurse‐led fracture liaison service (FLS) models of post‐hip fracture care compared with usual care. Analyses were conducted from a health care and personal social services payer perspective, using a Markov model to estimate the lifetime impact of the models of care. The base‐case population consisted of men and women aged 83 years with a hip fracture. The risk and costs of hip and non‐hip fractures were derived from large primary and hospital care data sets in the UK. Utilities were informed by a meta‐regression of 32 studies. In the base‐case analysis, the orthogeriatric‐led service was the most effective and cost‐effective model of care at a threshold of £30, 000 per quality‐adjusted life years gained (QALY). For women aged 83 years, the OG‐led service was the most cost‐effective at £22, 709/QALY. If only health care costs are considered, OG‐led service was cost‐effective at £12, 860/QALY and £14, 525/QALY for women and men aged 83 years, respectively. Irrespective of how patients were stratified in terms of their age, sex, and Charlson comorbidity score at index hip fracture, our results suggest that introducing an orthogeriatrician‐led or a nurse‐led FLS is cost‐effective when compared with usual care. Although considerable uncertainty remains concerning which of the models of care should be preferred, introducing an orthogeriatrician‐led service seems to be the most cost‐effective service to pursue. © 2016 American Society for Bone and Mineral Research.